The impact of vessel presence and noise on foraging behaviors in southern resident killer whale populations: a literature review (2017-2024) - McNeil, Caitlin, author (Colorado State University. Libraries, 2024)
Marine noise pollution is recognized as a potential barrier to successful foraging to Southern Resident Killer Whale (SRKW) populations off the coast of the U.S.A and Canada in the Salish Sea. The background noise seen in the primary summer and fall waters of the SRKWs is between 90-110 decibels (dB). For reference, human background noise levels are around 70 dB. High noise levels can be attributed to ferries, vehicle carriers, recreational vessels, container ships, and bulk carriers. This literature review employed thirteen sources that looked at foraging behavior near a local State Park where boat use is highly limited, the impacts to foraging seen when vessel are present, and the mitigation factors that can be applied to limit the observed impacts on SRKW foraging due to vessel presence. The results indicate that a mandatory vessel slow down through the Haro Strait could be beneficial for the reduction of noise and subsequent efficacy of foraging behaviors.
Department of Environmental & Radiological Health Sciences (ERHS).
Keywords: foraging; foraging behavior; southern resident killer whale; SRKW; vessel presence; noise; marine noise pollution